Nonablative Fractional Laser Resurfacing - Moravvej, Hamideh; Barikbin, Behrooz; Ghavam, Seyed Alireza; Karimi, Soheil (Journal of Lasers in Medical Sciences, 2011)
The desire to achieve cosmetic rejuvenation and reduce effects of aging and photodamage urged scientists to develop effectual techniques which have minimal side effects and impressive long-term efficacy. Traditional ablative resurfacing laser therapy has been used for several years;however, it has harmful side effects on the patient’s skin such as dyspigmentation, persistent erythema, infections, acneiform eruptions and scarring. It also prolongs downtime, so it puts a significant burden on society. Nonablative resurfacing laser therapy declines side effects of traditional therapies, although it has lower effectiveness in comparison with ablative one.Nonablative fractional resurfacing laser therapy commenced a modern technique which diminished side effects, while maintains the efficacy of traditional methods. The aim of of this current review is to sum up nonablative fractional laser therapies used for skin photorejuvenation at the past and present time and to evaluate the indications,advantages and classification of it and non-fractional resurfacing laser therapy